1998
DOI: 10.1183/09031936.98.12020351
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antimicrobial chemotherapy on spirometric parameters and pro-inflammatory indices in severe pulmonary tuberculosis

Abstract: Patients who have completed a treatment for severe pulmonary tuberculosis (TB) are often left with severe respiratory disability. There have been few prospective studies assessing the effect of treatment on lung function in such patients. The influence of antimicrobial chemotherapy on lung function was investigated over a six month period in patients with newly diagnosed pulmonary TB to test the hypothesis that treatment improves lung function, as well as to identify factors that may influence lung function ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
123
3
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 18 publications
5
123
3
9
Order By: Relevance
“…(1) When there are PF alterations due to pleural TB sequelae, mild restrictive ventilatory disorder is predominant, and pleural thickening of at least 10 mm increases the probability reduced lung volumes. (5,14) We had only two cases of pleural TB sequelae and access to the chest X-ray in only one of those two cases. The same situation was encountered in the three cases of pleuropulmonary TB sequelae, and it was not possible to evaluate the data found.…”
Section: Discussionmentioning
confidence: 99%
“…(1) When there are PF alterations due to pleural TB sequelae, mild restrictive ventilatory disorder is predominant, and pleural thickening of at least 10 mm increases the probability reduced lung volumes. (5,14) We had only two cases of pleural TB sequelae and access to the chest X-ray in only one of those two cases. The same situation was encountered in the three cases of pleuropulmonary TB sequelae, and it was not possible to evaluate the data found.…”
Section: Discussionmentioning
confidence: 99%
“…Lastarria y Salazar (23) han podido realizar espirometrías en pacientes con TBP activa, demostrando respuesta adecuada a broncodilatadores del tipo salbutamol y bromuro de ipratropio. Estos resultados han sido evaluados por Plit (24), quien reporta que la utilización de fármacos antituberculosos mejora la función pulmonar, al disminuir el daño parenquimal y con ello los índices pro-inflamatorios. En nuestro estudio, hemos encontrado que la alteración obstructiva sin reversibilidad o con reversibilidad parcial a los broncodilatadores fue la más frecuente.…”
Section: Discussionunclassified
“…Estos hallazgos, que relacionan la existencia de enfermedad obstructiva de la vía aérea por espirometría en pacientes con secuelas de tuberculosis pulmonar están de acuerdo con lo descrito previamente en otros estudios. (4,5,8,17,19,21,23,24,26,27).…”
Section: Discussionunclassified
“…Association between moderate and far advanced radiological lesions and lung function abnormalities like reduced PEFR has been reported in some studies 15 . Plit et al has found that the radiographic score at the beginning and after completion of treatment was related to Forced Expiratory Volume in first second 16 . A bronchodilator response is reported to be lesser in post tuberculosis patients compared to other obstructive airway disorders 17 .…”
Section: Associated Factors In Airflow Obstructionmentioning
confidence: 99%